ANÁLISE DA PERCEPÇÃO DOS USUÁRIOS SOBRE MELHORIAS CONSTRUTIVAS REALIZADAS EM HABITAÇÕES PRECÁRIAS EM MACEIÓ, ALAGOAS - Omena, Polyanna; Sampaio, Thaisa (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Urbanization process reached slopes and valleys in the city of Maceió. In these places, houses are made by self-construction, without any professional guidance and even with inadequate materials, making them extremely precarious. This article aims to verify the users satisfaction with the constructive improvements carried out by the public authority in a sample of subnormal dwellings in Grota da Macaxeira, Maceió - AL. The methodological procedures were based on documentary research and data analysis obtained in loco. The sample was delimited into 5 subnormal dwellings. After improvements made, the houses left the condition of extreme precariousness. Despite the punctual reforms, the residents showed great satisfaction in having their homes included in the Vida Nova nas Grotas Program. Conclusions suggests additional quality criteria to be included in the program.